Nursing and environment: a bibliographic review - Silviamar Camponogara; Cibelle Mello Viero; Graciele Erthal; Gabriela Camponogara Rossato (Universidade Federal de Santa Maria, 2011)
The study aimed identify national scientific production on nursing and environment interface. This is a descriptive bibliographical research, whose data were collected in the databases SCIELO and LILACS, BDENF. This study's body analysis consisted in 32 articles published in nursing periodicals in the period 1993-2010. The articles' analysis enabled to evidence three main categories existence: Educational Actions Development, Professional Training and Health Services' Solid Waste Management. It was concluded that Nursing field should approach the environmental thematic, proposing pedagogical strategies that involve professionals' awareness